Global Warming, Desertification/Degradation, and Droughts in Arid Regions - A. Zolotokrylin N.; А. Золотокрылин Н. (Izvestiya Rossiiskoi akademii nauk. Seriya geograficheskaya, 2019)
Applications of the concept of climatic desertification are considered. They include an approach to a separate assessment of aridization and degradation of arid lands and an approach to identifying “islands” of desertification from satellite data. It is established that the contribution of anthropogenic land degradation to desertification is confirmed by a significant linear trend of interannual fluctuations of satellite indicators of pasture digression in all the studied arid areas of Russia and Mongolia in the period 2000-2016. Significant trends in the intensification of aridization were characteristic only for a part of arid areas. Because of the excessive pastoral digression in arid areas, “islands” of desertification of anthropogenic origin are formed. The lifetime of such “islands” is determined by human influence and fluctuations in the humidity of the climate. An additional factor in the short-term decline in the life of the “islands” in Mongolia is the catastrophic death of livestock as a result of natural disasters (drought, zuta). The “island” of desertification, of natural origin, is found in the reserved part of the Sonora Desert, where rainy seasons and droughts determine the spread of aridization. Particular attention is paid to the analysis of trends in climatic characteristics. The increase in air temperature occurred in all the areas under study. Negative trends in annual and seasonal precipitation dominated the steppe zone of Russia during the periods 1936-1960 and 1991-2016, when the surface temperature of the North Atlantic was above normal. On the contrary, positive precipitation trends, weakening aridization, were observed in the period 1961-1990, corresponding to a temperature below the norm. Рассмотрены приложения концепции климатического опустынивания, включающие подход к раздельной оценке аридизации и деградации аридных земель и подход к идентификации “островов” опустынивания по спутниковым данным. Установлено, что вклад антропогенной деградации земель в опустынивание подтверждается значимым линейным трендом междугодовых колебаний спутниковых показателей пастбищной дигрессии во всех исследуемых аридных районах России и Монголии в период 2000—2016 гг. Усиление аридизации характерно только для части аридных районов. По причине чрезмерной пастбищной дигрессии здесь образуются “острова” антропогенного опустынивания, время жизни которых определяется влиянием человека и флуктуациями осадков. Дополнительным фактором кратковременного уменьшения жизни “островов” в Монголии служит катастрофический падеж скота в результате природных бедствий (засухи, дзута). “Остров” опустынивания природного происхождения обнаружен в заповедной части пустыни Сонора, где сезоны дождей и засух определяют распространение аридизации. Особое внимание уделено анализу трендов климатических характеристик. Повышение температуры воздуха произошло во всех сравниваемых районах исследования, отрицательные тренды осадков доминировали в степной зоне России в периоды 1936—1960 и 1991—2016 гг., когда температура поверхности Северной Атлантики была выше нормы. Напротив, положительные тренды осадков, ослабляющие аридизацию, наблюдались в период 1961—1990 гг.